FUZZY FACTORS CONSIDERATION FOR THE OPTIMIZATION OF THE WASTE COLLECTION ROUTE IN THE TERRITORIAL COMMUNITY - Khasivalieva, Iryna; Mesyura, Volodymyr (Scientific Works of Vinnytsia National Technical University, 2023)
The paper considers the process of the creation of the information technology module for the optimization of the waste collection process in the communities. The given module determines the expediency of inclusion of the waste containerbin to the route of the dust cart, depending on the degree of loading of the container and impact of the external factors on its availability, determined by the intensity of the traffic on the road to the container and state of the road, connected with weather conditions. Objective of the research consists in automatic determination of those waste containers which do not need urgent waste removal, that is an important component of theoptimization problem for the formation of the most reasonable routes for waste transportation. Scientific task of the researchincludes: determination of the factors, influencing the relevance of the waste removal problem; substantiation of the expediency of using fuzzy logic for this purpose; formation of fuzzy linguistic variables and construction of fuzzy knowledge base; study the efficiency of the process of fuzzy logic conclusion, regarding the determination of the relevance of the containers removal on the base of the suggested influencing factors; conclusion concerning the rationality of the suggested approach. The process of the relevance calculation of the inclusion the waste containers into the route of the waste collection, taking into account the degree of their filling and availability by means of fuzzy logic tools is described. Analysis of the external factors, influencing the relevance of the waste collection from the specific container is performed. Fuzzy graph model is suggested, the model presents possible routes of the dust carts, linguistic variables are given, membership functions of their terms are formed, fragment of the knowledge base, supplied by the production rules, processes of the fuzzification and defuzzification are graphically illustrated using Mamdani fuzzy inference algorithm. Calculation of the actuality index of the waste collection is given on the specific example. Testing has been performed on the base of the data of trash enclosures in the city of Rivne. As a result of elimination ща non-actual containersfrom the route the length of the routes was cut by on average 10.43 %. Further improvement of the routes formation is possible, taking into account the degree of importance of the waste collection, for instance, such as from hospitals, schools, recreation spaces and other civil objects.